Utility of deceased donor cultures in solid organ transplantation in preventing donor‐derived bacterial and fungal infectious diseases transmission. Issue 2 (7th February 2023) - Boutin, Catherine‐Audrey; Pouch, Stephanie M.; Ison, Michael G.
Abstract: Deceased donor and organ perfusion fluid cultures are obtained in order to inform recipient antimicrobial management and therefore reduce the risk of donor‐derived bacterial and fungal infections. However, important heterogeneity exists in laboratory practice across organ procurement organizations and clinical management of culture results across transplant centers. While not standardized, the clinical approach to donors with positive bacterial and/or fungal cultures should be informed by the risk of donor‐derived infection (DDI) and the consequence of organ non‐utilization and account for potential unintended effects of antimicrobial use in the recipient. In this review, we summarize the literature on bacterial and fungal DDIs, describe the significance of positive cultures by anatomic site, and summarize current guidance on the management of positive cultures from donors or preservation fluids.